A risk modeling framework to evaluate the impacts of climate change and adaptation on food and water safety. (February 2015) - Smith, Ben A.; Ruthman, Todd; Sparling, Erik; Auld, Heather; Comer, Neil; Young, Ian; Lammerding, Anna M.; Fazil, Aamir
Abstract: Climate change may be a factor leading to increased risks of food- and waterborne illnesses from consumption of existing and emerging biological hazards. It is beneficial to develop integrated approaches to evaluate, and provide scientific assessments of, potential climate change adaptation measures to inform risk management related to climate and weather events. To this end, a risk modeling framework was created to facilitate estimations of the impact of weather and climate change on public health risks from biological hazards in food and water and to compare potential adaptation and risk mitigation strategies. The framework integrates knowledge synthesis methods, data storage and maintenance, and stochastic modeling. Risk assessment models were developed for food and water safety case studies for demonstrative purposes. Scenario analyses indicated that implementing intervention measures to adapt to changing climate impacts might mitigate future public health risks from pathogens to varying degrees. The framework brings a generic approach to allow for comparison of relative public health risks and potential adaptation strategies across hazards, exposure pathways, and regions to assist with preventive efforts and decision-making. Highlights: Framework to model adaptation to climate change impacts on food and water safety. Integrates narrative and systematic review, databases, and stochastic modeling. Preliminary Cryptosporidium and Giardia, mycotoxin, and Vibrio models were developed. Reductions in risks from potential risk mitigation measures were estimated. Compares relative risks and evaluates interventions through risk assessment models.